Perintah untuk Menghormati Ayah dan Ibu: Suatu Tinjauan Moralitas Dekalog - Megawati Naibaho (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2025)
Every generation complaining the young people in this new era lack of respect towards parents. The young people tend to seek pleasure and pay less attention to manners, especially in relationships with parents. The command to honor one's parents is actually an obligation that God even conveyed to Moses as the leader of the Nation of Israel in the Decalogue. The purpose of this writing is to explain the noble meaning and value of honoring fathers and mothers as stated in the Decalogy. The method used is a combination of two methods, namely qualitative and quantitative research methods. By digging up information from primary and supporting sources and accountable references. The expected result of the research is that the author can present briefly, clearly and systematically the idea of the morality of the act of respecting fathers and mothers. Thus, it is hoped that this research will be a good source of information so that readers will know more about the importance of respecting fathers and mothers and can realize it in daily life.